Establishment Of Indigenous People Owned Enterprises As A Form Of Community Corporate In Sumbawa Regency - Ahmad Yamin; Geatriana Dewi (Faculty of Law, University of Mataram, 2022)
Indigenous People Owned Enterprises are basically business entities which managing two roles, both as a natuurlijke persoon and recht persoon. In the other hand, it also works as an economic provider along as juridical benefits to members, which leads to encourage economic independence and mutual prosperity. This paper aims to build the economic independence of indigenous peoples through the construction of BUMMA which was formed by indigenous women. The approach method applied within this study is statute approach by applicating the combination of library research with social approach for indigenous women in each indigenous community in Sumbawa Regency. The results obtained by the research is BUMMA as natuurlijke persoon en rechtspersoon is a fresh approach in managing business entities at the level of customary law which worthwhile from, by, and for indigenous women. The existence of BUMMA as a part of customary law communities and as a form of community corporation is a new form of economic institution nowaday in attempt to develop independence and the welfare of indigenous women as part of the customary law community.